Local Taxes, Regulations, and the Business Environment : Finding the Right Balance - Corthay, Laurent (World Bank, Washington, DC, 2012)
Regional and municipal governments play a key role in establishing a local business environment that is attractive to foreign and domestic investors. However, in many countries, entrepreneurs face a complex web of local taxes, regulatory fees, and other charges. This situation increases the costs and risks of doing business, thus limiting the potential for business growth, investment, and job creation. This note explores the roots of this problem and introduces options for addressing it.